On tropical cyclone frequency and the warm pool area - R. E. Benestad (Copernicus Publications, 2009)
The proposition that the rate of tropical cyclogenesis increases with the size of the "warm pool" is tested by comparing the seasonal variation of the warm pool area with the seasonality of the number of tropical cyclones. An analysis based on empirical data from the Northern Hemisphere is presented, where the warm pool associated with tropical cyclone activity is defined as the area, A , enclosed by the 26.5°C SST isotherm. Similar analysis was applied to the temperature weighted area A T with similar results. An intriguing non-linear relationship of high statistical significance was found between the temperature weighted area in the North Atlantic and the North-West Pacific on the one hand and the number of cyclones, N , in the same ocean basin on the other, but this pattern was not found over the North Indian Ocean. A simple statistical model was developed, based on the historical relationship between N and A . The simple model was then validated against independent inter-annual variations in the seasonal cyclone counts in the North Atlantic, but the correlation was not statistically significant in the North-West Pacific. No correlation, however, was found between N and A in the North Indian Ocean. A non-linear relationship between the cyclone number and temperature weighted area may in some ocean basins explain both why there has not been any linear trend in the number of cyclones over time as well as the recent upturn in the number of Atlantic hurricanes. The results also suggest that the notion of the number of tropical cyclones being insensitive to the area A is a misconception.